2020
DOI: 10.3389/fonc.2020.00346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Elements Spine SRS Plan Quality for SRS and SBRT Treatment of Spine Metastases

Abstract: Purpose: The Elements Spine Stereotactic Radiosurgery treatment planning system uses automated volumetric modulated arc radiotherapy that can provide a highly conformal dose distribution to targets, which can provide superior sparing of the spinal cord. This study compares the dosimetric quality of Elements plans with the clinical plans of 20 spine stereotactic radiosurgery/stereotactic body radiation therapy (SRS/SBRT) patients treated at our institution. Methods: Twenty spine SRS/SBRT patients who were clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Previous evaluation studies have shown the advances of Elements Spine SRS in dosimetry (15)(16)(17). Moreover, the autosegmentation tool Elements SmartBrush Spine (ESS) was developed for fast target delineation, which can potentially improve the efficiency of the clinical workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evaluation studies have shown the advances of Elements Spine SRS in dosimetry (15)(16)(17). Moreover, the autosegmentation tool Elements SmartBrush Spine (ESS) was developed for fast target delineation, which can potentially improve the efficiency of the clinical workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative algorithms for the automation of treatment planning have been implemented for spine SBRT (19)(20)(21)(22). Compared with these alternative methods, the Autoplanning and Personalized engines present a clear advantage.…”
Section: Discussionmentioning
confidence: 99%
“…( 20 ) explored the feasibility of knowledge-based planning strategy using Varian RapidPlan software for 10 spine SBRT cases, reporting an overall improved quality and a decrease of total planning time from approximately 1.5 h to 15 min. Last, a dedicated TPS, the Elements Spine SRS (Brainlab AG, Munich, Germany), has been recently evaluated for the generation of automated quality plans in spine SBRT ( 21 , 22 ). Comparison with previous clinical plans obtained with other TPS resulted in sharpest dose gradient and in lower spinal cord maximum point doses.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, specialized planning solutions are also elaborated. The Elements TPS (Brainlab, Munich) has been developed according to this philosophy, with specific modules dedicated to stereotactic radiosurgery (SRS): Cranial SRS, Multiple Brain Mets SRS or Spine SRS [6], [7]. Elements Spine SRS (E-SRS) allows an automated VMAT planning process, based on the use of templates defining beam geometry and dosimetric objectives on organs at risk (OAR) and target volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization algorithm includes an arc duplication option enabling PTV splitting into several low complexity elementary volumes treated separately with one or several arc each. Such a decomposition should also result in treatment plans with the same or higher quality than non-dedicated TPS [6]. Another advantage of E-SRS is that the planning process is semi-automated.…”
Section: Introductionmentioning
confidence: 99%